Modulation of antioxidant enzyme gene expression by extremely low frequency electromagnetic field in post-stroke patients. (17th November 2018) - Cichon, Natalia; Bijak, Michal; Synowiec, Ewelina; Miller, Elzbieta; Sliwinski, Tomasz; Saluk-Bijak, Joanna
Abstract: Oxidative stress plays the most important role in the pathogenesis of stroke. Extremely low frequency electromagnetic field (ELF-EMF) therapy may be complementary in post-stroke therapy, as it modulates oxidative stress. The aim of this study was to evaluate the messenger ribonucleic acid (mRNA) levels of certain antioxidant genes in post-stroke patients given ELF-EMF therapy. Forty-eight post-stroke patients were divided into two groups: an ELF-EMF group and a non-ELF-EMF group. All patients underwent the same program of physical therapy, but the ELF-EMF group was additionally given ELF-EMF treatment. In order to determine the level of gene expression, we evaluated the level of mRNA expression of catalase, superoxide dismutase, and glutathione peroxidase. We observed that after ELF-EMF therapy, the mRNA expression of the studied genes ( CAT, SOD1, SOD2, GPx1, and GPx4 ) significantly increased, which enhanced the antioxidant defence of the body. ELF-EMF therapy intensifies the endogenous antioxidant system by increasing the mRNA expression of genes encoding antioxidant enzymes and enhances the effectiveness of post-stroke patient therapy.